UPAYA PENINGKATAN KETERAMPILAN MENULIS PUISI MELALUI TEKNIK ALIH WAHANA NASKAH DRAMA BERBANTUAN MEDIA TRANSFORMASI KALIMAT MAJAS PADA SISWA KELAS XI-1 SMAN 2 JEMBER - Roro Ramadhanty Putri Khoirunissa, Raden; Mijianti, Yerry; Santoso, Agus (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Writing poetry is a language skill that requires the ability to choose diction and use figures of speech so that ideas can be conveyed in an imaginative, expressive, and aesthetically pleasing manner. However, students still struggle to transform their ideas into poetic language. This study aims to improve poetry-writing skills through the application of the drama script adaptation technique, aided by media for transforming figurative language sentences, among students in Class XI-1 at SMAN 2 Jember. The study employed a mixed-methods approach that combined a descriptive qualitative approach with the Kemmis and McTaggart model of Classroom Action Research (CAR), conducted over two cycles. Data were collected through poetry writing tests, observations, interviews, and field notes. The results showed that the application of the drama script adaptation technique, supported by media for transforming figurative language, was able to improve both the process and outcomes of students’ poetry writing skills. The mastery of figurative language use increased from 28.57% in the pre-cycle to 65.71% in Cycle I and 91.43% in Cycle II, while the use of diction increased from 37.14% to 68.57% and 91.43%. The aspect of content alignment with the theme improved from 77.14% to 88.57% and 100%; idea development improved from 57.14% to 77.14% and 94.29%; and the coherence of the poem’s lines improved from 48.57% to 77.29% and 94.29%. In addition, students became more active, confident, and capable of transforming dialogue from a play into more poetic lines of verse. Thus, the technique of adapting a play script using media for transforming figurative language is effective as an alternative learning method to improve poetry-writing skills in high school.